2010
DOI: 10.1017/s095927091000033x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid declines in habitat quality and population size of the Liben (Sidamo) Lark Heteromirafra sidamoensis necessitate immediate conservation action – ERRATUM

Abstract: Figure 5 of the above paper (Donald et al., 2010) was printed in black and white rather than colour. The publishers apologise for this error, and have reprinted the image below correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…Fuhlendorf et al 2009). Our study demonstrates that grass height and cover or each one alone, depending on the habitat requirements of individual species, determines habitat use by birds (Winter et al 2005;Devereux et al 2006;Donald et al 2010). Regional studies that link species abundance to habitat do not take into account detection (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…Fuhlendorf et al 2009). Our study demonstrates that grass height and cover or each one alone, depending on the habitat requirements of individual species, determines habitat use by birds (Winter et al 2005;Devereux et al 2006;Donald et al 2010). Regional studies that link species abundance to habitat do not take into account detection (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…In the 1970s, a shift in government policy encouraged permanent settlement in place of transhumance, thereby increasing grazing pressure and eventually triggering cereal cultivation (Tilahun et al 2017). Anecdotal evidence, particularly the testimony of elders we have interviewed, indicated that by 2010 the grassland on the plain was already much degraded in terms of structure and grass species diversity compared to a generation earlier (Donald et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The Liben Plain is one of only two known sites for Liben Lark Heteromirafra archeri , also known as Archer’s or Sidamo Lark (Collar 2009, Spottiswoode et al 2009, 2013, Donald et al 2010). A limited survey in October 2019 of the second site, near Jijiga in north-eastern Ethiopia, suggested that very few birds remain there (Negussie Toye and Abiy Dagne pers.…”
Section: Introductionmentioning
confidence: 99%
“…Grass height and cover are proximate factors influencing habitat selection and nest survival amongst grassland birds (Devereux et al, 2008;Cao et al, 2009;Donald et al, 2010;Fisher & Davis, 2010;Klug, Jackrel & With, 2010). Several species of conservation concern occur with conflicting habitat requirements in our study region (Maphisa et al, 2009(Maphisa et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%